A multi-methods study exploring the role of stakeholders in the digital preservation environment: The case of Ghana - Adu, K.K.; Adjei, E. (The Electronic Library, 2018)
This study aims to examine the role of stakeholders in the digital preservation under the following key research questions: What are the levels of awareness of the volumes of digital material? What are the contributory factors for the growth of digital records and the types of information and communication technology products? Design/methodology/approach With the convergence of questionnaire, documentary evidence, observation, interview and questionnaire, this paper aims to examine the state and role of stakeholders in the digital preservation environment. The adoption of the multi-methods approach to the study offered a panoramic view of the inquiry where the quantitative paradigm became the emphasis or the priority for the study, while the qualitative data set provided a secondary or supportive role. Findings The study underscored the adoption of collaborative and participatory opportunities in the digital preservation environment and reinforced the concept of Open Data, which thrives on citizen’s trust, participation and collaboration (UN e-government survey, 2014). It further revealed lack of knowledge about the likely growth of digital material across the ministries and agencies and confirmed that government legislations have contributed to the increased demand for information and the growth of digital records. Originality/value The study underlined two mutually exclusive concepts (collaboration and participation) as part of the strategies to ameliorate the digital preservation conundrum confronted by memory institutions in Ghana. The applications of these concepts as solutions to the digital preservation problems are novel and currently gaining prominence and acceptance within the archival community Their adoption in this study could not have come at a better time, particularly when public sector organizations are confronted with the challenge of preserving digital records.
Keywords: Ghana; Government; Data storage; Archives management; Preservation; Born digital materials